Impact of moisture and grinding on yield, physical, chemical and thermal properties of wholegrain flour obtained from hydrothermally treated sorghum grains - Acquisgrana, María del Rosario (2020)
The present work evaluates the potential of sorghum with high content of tannins for wholegrain flour production. Two types of mills were used: a roller mill (RM) and a blade (BM) mill. The impact of moisture and grinding on yield, physical, chemical and thermal properties were evaluated. Maximum yield was obtained using a BM with 25% moisture in the grain, resulting in 60.9% versus 28% (g flour g−1 of wholegrain sorghum) for the RM. Grain moisture and milling type affected flour colour and ashes. For both mills, the pasting and thermal properties of flour with grain moisture variation were significantly different from the untreated control sample. By studying the procedures for flour production and quality characteristics, it is possible to produce flour with good physical attributes, which can contribute to the development of gluten‐free foods based on sorghum for the coeliac population.